Combination of Fourier Transform Infrared (FTIR) with chemometrics for halal authentication of face mask products made from gelatin - Nina Salamah; Rabiatul Adawiyah; Any Guntarti; Hari Susanti (BIO Web of Conferences)
Porcine gelatin is often used to replace bovine gelatin because its production costs are more affordable, so there are concerns about contamination with haram ingredients such as porcine, along with the boom in face mask products circulating in Indonesia. This research was conducted to determine the origin of gelatin in facial mask products using the differences in the functional groups of bovine and porcine gelatin. Reference face mask samples were made with a concentration variation ratio of pure bovine gelatin and pure porcine gelatin of 1:0; 0.75:0.25; 0.50:0.50; 0.25:0.75; and 0:1. The gelatin contained in reference face mask samples and face mask samples circulating on the market was isolated with acetone, which was then carried out by a vortexing process and centrifuged to obtain the supernatant. The supernatant obtained was then analyzed using the Fourier transform infrared (FTIR) method to determine the absorbance value and wave number. Next, it was analyzed further using chemometrics. The results of the FTIR analysis showed the compound composition of gelatin consisting of groups O-H, C-N, C=O, C-H, and C-O. The number of waves in the 1235–1077 cm-1 optimization result was used for the PLS and PCA analyses. PCA analyses showed that one gelatin mask product was in a square with gelatin masks used as porcine gelatin references, while the other two samples were outside the bovine and porcine gelatin quadranes. The conclusion of this study was that of the three samples of facial masks studied, one came from porcine gelatin, and the other two were of unknown gelatin origin.